The dimerization of methyl vanillate improves its effect against breast cancer cells via pro-oxidant effect - Pessoa, Adriano de Souza; Tokuhara, Cintia Kazuko; Fakhoury, Vanessa Svizzero; Pagnan, Ana Lígia; Oliveira, Gabriela Silva Neubern de; Sanches, Mariana Liessa Rovis; Inacio, Kelly Karina; Costa, Bruna Carolina; Ximenes, Valdecir Farias [UNESP]; Oliveira, Rodrigo Cardoso de (Elsevier, 2022)
Phenolic phytochemicals are a group of organic compounds with potent antioxidant features but can also act as powerful pro-oxidants. These characteristics are effective in reducing metastatic potential in cancer cells, and this effect has been associated with reactive oxygen species (ROS). Methyl vanillate (MV) and its dimer, methyl divanillate (DMV), are potent antioxidants. In the present study, we investigated the effects of MV and DMV on breast cancer cell lines MCF-7 and MDA-MB-231 and compared the results using the non-tumor cell line HB4a. Our results indicated that the compounds performed a pro-oxidant action, increasing the generation of ROS. DMV decreased the viability cell, showing a higher apoptotic effect and inhibition of proliferation than MV on both cell lines, with significant differences between groups (p < 0.05). Some modulation of NOX4, NOX5, and DUOX were observed, but the results did not correlate with the intracellular production of ROS. The dimer showed more effectivity and pro-oxidant effect than MV, impacting cell line MCF-7 in higher extension than MDA-MB-231. In conclusion, and corroborating with reported works, the dimerization of natural phenolic compounds was associated with improved beneficial biological effects as a potential cytotoxic agent to tumor cells.
Keywords: Methyl divanillate; Methyl Vanillate; Pro-oxidant